El espejo de la ekphrasis Más acá de la imagen. Más allá del texto. - De la Calle, ROMÁN (Escritura e Imagen, 2005)
Since the Second Sophistry the ekphrasis, the literary description of images, has been assimilated. From the point of view of art criticism the author of this work proposes a new ekphrasis in a defense of description, like a constitutive element of criticism or propedeutic resource. The hypotiposis, the formation of pictorial images through words, will be also studied. In the base of the ekphrasis, as in the hypotiposis, is the description. This work leads us through three related aspects of the development of the ekphrasis: the relations between description and narration; the exchanges between titles and works; and finally, the tensions between the descriptive and interpretative functions. The validity of the ekphrasis in front of the contemporary artistic experience will be discussed considering the incompleteness principle of G.C. Argan and the principle of the transparence of S. Sontag. The connection between image and text, understood as a crossroad full of parallelisms, is taken as a fundamental part of the epistemology of criticism.